Comment l’île Maurice est-elle devenue Covid free ? - Nathalie Bernardie-Tahir (EchoGéo)
After being affected by the COVID-19 epidemic in March 2020 and having implemented a whole series of sanitary measures, Mauritius has become, for more than ten months, one of the few Covid-free States on the planet, until a new epidemic wave hits it again in March 2021. The objective of this reflection is to understand how this Indian Ocean Small Island Developing State (SIDS) has succeeded, where the great powers of the north have so far failed. While SIDS are often represented as vulnerable places, one's can consider, on the contrary, that the relative island remotness and small size of Mauritius combined with a strong state interventionism have been major assets in the spatial control of the pandemic and its containment.